To simplify the expression \(\sqrt{4396} + \sqrt{44} - \sqrt{2275}\), we first need to simplify each radical if possible.
-
Simplifying \(\sqrt{4396}\): \[ 4396 = 4 \times 1099 \] \[ \sqrt{4396} = \sqrt{4 \times 1099} = \sqrt{4} \times \sqrt{1099} = 2\sqrt{1099} \]
-
Simplifying \(\sqrt{44}\): \[ 44 = 4 \times 11 \] \[ \sqrt{44} = \sqrt{4 \times 11} = \sqrt{4} \times \sqrt{11} = 2\sqrt{11} \]
-
Simplifying \(\sqrt{2275}\): \[ 2275 = 25 \times 91 = 25 \times (7 \times 13) \] \[ \sqrt{2275} = \sqrt{25 \times 91} = 5\sqrt{91} \]
Now we can substitute back into the expression: \[ 2\sqrt{1099} + 2\sqrt{11} - 5\sqrt{91} \]
Since \( \sqrt{1099} \), \( \sqrt{11} \), and \( \sqrt{91} \) are all unlike radicals, we cannot combine them into a single radical expression. Thus, we write the expression as: \[ 2\sqrt{1099} + 2\sqrt{11} - 5\sqrt{91} \]
The expression is in simplest radical form and nothing can be combined further.
Thus, the answer is: Unlike radicals cannot be combined using addition.